ZapE/Afg1 interacts with Oxa1 and its depletion causes a multifaceted phenotype - Pyrih, Jan; Rašková, Vendula; Škodová-Sveráková, Ingrid; Pánek, Tomáš; Lukeš, Julius (PLoS One, 2020)
ZapE/Afg1 is a component of the inner cell membrane of some eubacteria and the inner mitochondrial membrane of eukaryotes. This protein is involved in FtsZ-dependent division of eubacteria. In the yeast and human mitochondrion, ZapE/Afg1 likely interacts with Oxa1 and facilitates the degradation of mitochondrion-encoded subunits of respiratory complexes. Furthermore, the depletion of ZapE increases resistance to apoptosis, decreases oxidative stress tolerance, and impacts mitochondrial protein homeostasis. It remains unclear whether ZapE is a multifunctional protein, or whether some of the described effects are just secondary phenotypes. Here, we have analyzed the functions of ZapE in Trypanosoma brucei, a parasitic protist, and an important model organism. Using a newly developed proximity-dependent biotinylation approach (BioID2), we have identified the inner mitochondrial membrane insertase Oxa1 among three putative interacting partners of ZapE, which is present in two paralogs. RNAi-mediated depletion of both ZapE paralogs likely affected the function of respiratory complexes I and IV. Consistently, we show that the distribution of mitochondrial ZapE is restricted only to organisms with Oxa1, respiratory complexes, and a mitochondrial genome. We propose that the evolutionarily conserved interaction of ZapE with Oxa1, which is required for proper insertion of many inner mitochondrial membrane proteins, is behind the multifaceted phenotype caused by the ablation of ZapE.
Keywords: Phylogeny; biotinylace; Protein Binding; Genome, Mitochondrial; Mitochondria; Biotinylation; Trypanosoma brucei brucei; genom mitochondriální; Phenotype; protozoální proteiny; delece genu; Electron Transport Complex I; mitochondrie; Electron Transport Complex IV; Gene Deletion; respirační komplex IV; fenotyp; Eukaryota; vazba proteinů; Protozoan Proteins; down regulace; Mitochondrial Proteins; fylogeneze; mitochondriální proteiny; Down-Regulation; respirační komplex I